Overview on modelling tools used in management strategies for invasive insect species (Bollettino di zoologia agraria e bachicoltura, 2024)
To deal with the increased frequency and magnitude of invasive species, risk-based strategies for decision-support are designed. In several strategic areas, modelling tools are indispensable and used among others, for the identification of risks (maps of potential distributions) and the analysis of treatment options (containment of already established species). This chapter provides a brief overview on modelling tools designed for describing the potential distributions of invasive species (statistical descriptions, mechanistic models) and their spread. With respect to the spread, modelling tools are developed on the basis of the mean-field assumption (statistical models, phenomenological models) and models that are not constraint by this assumption (continuous dynamic models, individual-based models, grid-based (lattice) models, metapopulation models).In the area of risk identification and potential distributions of invasive species, three tools are used. The first tool exclusively takes into account the climatic requirements of the invasive species, the second tool focuses on the population ecology and management, and the third tool treats them as members of communities and applies methods of community ecology to their study and management.In the area of the analysis of risk treatment options and the design of containment strategies, ecologists and entomologists also rely on a wide range of different methodologies. Some tools appear to be suitable for homogeneous environments and large-scale dispersal processes. Other models are appropriate for low density populations and high biological and environmental variability. There are also modelling tools that take into account spatial heterogeneity and fragmented landscapes. The selection of modelling tools depends on the quality of the ecological system under study and management as well as on the objectives to be met. In general, modelling tools are not seen as an end-product of a project but continuously changed in response to new information and needs.
Keywords: invasive species; model; risk identification; potential distribution; spread